2012
DOI: 10.1002/aoc.2925
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application of palladium stearates as precursors for the preparation of palladium nanoparticles

Abstract: This report successfully demonstrates the synthesis and application of palladium stearates. It was found that the branching of the carboxylate anion of metal precursors could influence the size and shape of palladium nanoparticles (PdNPs). Worm-like nanowires were formed when using the branched isomer palladium isostearate (PdISt 2 ), while triangular nanoparticles were produced in a majority when using the normal form: palladium stearate (PdSt 2 ). Furthermore, when applying CO 2 to the system, both types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The control of shape and size during platinum nanoparticle synthesis is an essential part of designing and studying catalyst materials with improved activity and selectivity. Recent studies which characterized catalysts' shapes and exposed surfaces indicate that surface structures can be altered to tune catalytic properties . It was also shown that high index facets on a catalyst surface may exhibit higher activities than lower index facets for certain reactions due to the decreased coordination of step edges and defects, but these sites can also be detrimental to other reactions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The control of shape and size during platinum nanoparticle synthesis is an essential part of designing and studying catalyst materials with improved activity and selectivity. Recent studies which characterized catalysts' shapes and exposed surfaces indicate that surface structures can be altered to tune catalytic properties . It was also shown that high index facets on a catalyst surface may exhibit higher activities than lower index facets for certain reactions due to the decreased coordination of step edges and defects, but these sites can also be detrimental to other reactions .…”
Section: Introductionmentioning
confidence: 99%
“…WCR has become one of the most common catalyst preparation methods due to the vastly controllable synthetic parameters . Early reports of this method go as far back as 1857 and can be used in systems of gold, palladium, cobalt and silver . Some of the earliest reports of Pt shape direction using WCR were reported in 1941 by Rampino and Nord and then later by El‐Sayed in 1996, but modifications and variations of these syntheses are still being developed today to design catalyst materials with enhanced properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different stabilizers employed in metal NP synthesis, fatty acids have been widely applied because of their high affinity to metals. In the synthesis of various metal NPs typical examples include lauric acid [17][18][19][20] , palmitic acid 17,21 , and stearic acid 17,22,23 . The most frequently applied fatty acid capping agent in metal NP synthesis is the unsaturated fatty acid oleic acid (OA), and its sodium salt form, sodium oleate (NaOL).…”
Section: Introductionmentioning
confidence: 99%